Comparison of the effects of adding fentanyl or remifentanil to propofol in colonoscopy sedoanalgesia on visual analog scale and recovery: A prospective double-blind study (Annals of Medical Research, 2021)
None
Keywords: Sedoanalgesia; Colonoscopy; Fentanyl; Remifentanil; Pain; Recovery.